Efficient yellow and green emitting InGaN/GaN nanostructured QW materials and LEDs. Issue 9 (25th April 2016) - Nakajima, Yoshitake; Lin, Yenting; Dapkus, Paul Daniel
Abstract : Efficient green emitting LEDs and monolithic white light emitting LEDs require the extension of the range of efficient light emission in the GaN/InGaN materials system. We demonstrate high efficiency green and yellow light emitting multiple quantum well (MQW) structures grown on GaN nanostripe templates. The structures show promise for realizing high efficiency phosphor – free white LEDs. The nanostripe dimensions range from 100 to 300 nm and have separations that range from 300 nm to 1 μm. The MOCVD growth conditions strongly affect surfaces expressed in the GaN nanostripes whose sidewalls can be controlled to be nearly vertical or inclined and intersecting. Single quantum well (QW) structures are grown on these different stripes. Photoluminescence (PL) measurement shows that QW grown on stripes with the {10−11} surfaces and triangular shape emit the longest peak wavelength and highly efficient PL emission peak wavelengths as long as 570 nm are realized. PL and electroluminescence (EL) spectra show narrow linewidth that is comparable to the planar case and CL studies further demonstrate the uniform emission wavelength along the sidewalls of the structures. Finally, we have grown and fabricated green emitting LEDs on {10−11} faceted nanostripes with promising device characteristics.